Study on Water Quality for Seaweed Cultivation in Desa Jawai Laut Sambas Regency West Kalimantan - Maunala, Adrian; Safitri, Ikha; Kushadiwijayanto, Arie Antasari; Sofiana, Mega Sari Juane (Sam Ratulangi University, 2023)
Desa Jawai Laut is a coastal village in Sambas Regency, West Kalimantan with the potential of marine waters that can support the community's economy. One of the activities carried out is the seaweed cultivation of Eucheuma cottonii using the longline method. The development of cultivation activities can be supported by optimal water conditions to support seaweed production. The aim of this study was to analyze the water quality in Desa Jawai Laut, Sambas Regency for the development of seaweed cultivation. Determination of location sites was carried out systematically, as many as 7 stations with a distance of 500 m. The water quality index was analyzed using the CCME-WQI method. The results showed that in general, the water quality of Desa Jawai Laut was in a good category with a CWQI value of 80. Stations I and IV were in the excellent category and were recommended as locations for the development of seaweed cultivation. Keywords: Seaweed cultivation, water quality, CWQI Abstrak Desa Jawai Laut merupakan desa pesisir di Kabupaten Sambas, Kalimantan Barat dengan potensi perairan laut yang dapat menunjang perekonomian masyarakat. Salah satu aktivitas yang dilakukan adalah budidaya rumput laut Eucheuma cottonii dengan metode longline. Pengembangan kegiatan budidaya dapat ditunjang dengan adanya kondisi perairan yang optimal untuk mendukung hasil produksi rumput laut. Penelitian ini bertujuan untuk menganalisis kualitas perairan di Desa Jawai Laut, Kabupaten Sambas untuk pengembangan budidaya rumput laut. Penentuan titik lokasi dilakukan secara sistematik, sebanyak 7 stasiun dengan jarak 500 m. Indeks kualitas air dianalisis menggunakan metode CCME-WQI. Hasil penelitian menunjukkan bahwa secara umum kualitas perairan Desa Jawai Laut dalam kategori baik dengan nilai CWQI 80. Stasiun I dan IV masuk ke dalam kategori sangat baik dan direkomendasikan sebagai lokasi untuk pengembangan budidaya rumput laut. Kata Kunci: Budidaya rumput laut, kualitas perairan, CWQI